The role of lipid metabolism in cognitive impairment - Meifang Xu; Liyuan Wang; Yun Meng; Guiqiong Kang; Qing Jiang; Tao Yan; Fengyuan Che (Arquivos de Neuro-Psiquiatria)
Alzheimer's disease (AD), diabetic cognitive impairment (DCI), and vascular dementia (VD) are considered the most common causes of severe cognitive impairment in clinical practice. Numerous factors can influence their progression, and many studies have recently revealed that metabolic disorders play crucial roles in the progression of cognitive impairment. Mounting evidence indicate that the regulation of lipid metabolism is a major factor in maintaining brain homeostasis. Generally, abnormalities in lipid metabolism can affect amyloid-beta (Aβ) deposition, tau hyperphosphorylation, and insulin resistance through lipid metabolic signaling cascades; affect the neuronal membrane structure, neurotransmitter synthesis and release; and promote synapse growth, which can impact neural signal transmission and exacerbate disease progression in individuals with cognitive impairment, including AD, DCI, and VD. Moreover, apolipoprotein E (APOE), a key protein in lipid transport, is involved in the occurrence and development of the aforementioned diseases by regulating lipid metabolism. The present article mainly discusses how lipid metabolic disorders in the brain microenvironment are involved in regulating the progression of cognitive impairment, and it explores the regulatory effects of targeting the key lipid transport protein APOE in the context of the role of lipid metabolism in the common pathogenesis of three diseases—Aβ deposition, tau hyperphosphorylation, and insulin resistance—which will help elucidate the potential of targeting lipid metabolism for the treatment of cognitive impairment.